Why do we need this? Perception and integration of basic and clinical sciences by dental hygiene students. - Chow, Ava K.; Friesen, Reid; Sharmin, Nazlee (Canadian Journal of Dental Hygiene, 2025)
Background: Integrating the basic sciences into a clinical curriculum is critical for students' understanding of physiological processes in patient care. Health professional students with a better understanding of basic science principles have better diagnostic accuracy and a more comprehensive understanding of clinical cases. Traditional health professional curricula offer discrete basic science and clinical courses, resulting in students who struggle to recognize the relevance of the material and incorporate fundamental science knowledge into their later clinical education. This study examined student perceptions of integrating foundational sciences into their health professional program and evaluated the extent of that integration with clinical oral medicine and pathology knowledge using a knowledge integration scale. Methods: Students in the second to fourth years of the Dental Hygiene Program at the University of Alberta, Canada, were invited to participate in an anonymous survey regarding their perceptions of the integration of sciences in teaching. In a separate invitation, third- and fourth-year dental hygiene students were invited to complete a graded measure of knowledge integration. Results: Significant differences were found between year cohorts in the perceptions of integrating basic sciences into the clinical curriculum. Content analysis of descriptive student comments revealed the benefits of integrating clinical and foundational science knowledge. There were no significant differences between third- and fourth-year dental hygiene students in measured integration of foundational science and clinical knowledge. Conclusions: Further studies are needed to shed light on faculty perceptions and identify strategies to facilitate curricular integrations at the faculty level.